2015
DOI: 10.1071/he14010
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy product sponsorship of Australian national and state sports organisations

Abstract: Issue addressed: Marketing of products harmful to the health of children has been found to be prolific, and occurs across multiple media platforms and in several settings, including organised sport, thus potentially undermining the health benefits inherent in sports participation. Through website audits, this study investigated the nature and extent of unhealthy food, beverage, alcohol and gambling sponsorship across peak Australian sporting organisations. Methods: A structured survey tool identified and asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Food and beverage companies exploit elite sports’ marketing potential, with prevalent sponsorship of various Australian sports through their governing bodies by companies promoting unhealthy food, alcohol and gambling products. This has led to calls for regulatory guidelines to be established to limit such sponsorship [9]. At the same time, opportunity exists for public health organisations to capitalise on elite sport sponsorship for reaching young adults with well-aligned healthier eating and body weight messages.…”
Section: Introductionmentioning
confidence: 99%
“…Food and beverage companies exploit elite sports’ marketing potential, with prevalent sponsorship of various Australian sports through their governing bodies by companies promoting unhealthy food, alcohol and gambling products. This has led to calls for regulatory guidelines to be established to limit such sponsorship [9]. At the same time, opportunity exists for public health organisations to capitalise on elite sport sponsorship for reaching young adults with well-aligned healthier eating and body weight messages.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the pervasiveness and effectiveness of unhealthy food and beverage advertising have been studied in several sports sponsorship settings. In the realm of children’s sport in Australia, half of food company sponsorships did not fulfill healthy sponsorship criteria [79], and 10% of national and state sports organizations in Australia have unhealthy food/beverage, alcohol, or gambling sponsors [80]. Moreover, an analysis of the sponsorship of community sports organizations showed that the majority of food company sponsors did not meet healthiness criteria ratings developed by a panel of 10 government officials and experts in nutrition, health promotion, physical activity, and health economics [81].…”
Section: The Psychology Of Sports Sponsorships Athlete Endorsementsmentioning
confidence: 99%
“…Event sponsorship positions a product or brand for a certain customer segment so that there is a match between the product or brand, and the demographics and psychographics of the event attendees. Sponsorship of sports teams and sporting events is one example (Macniven 2015). O’Brien and Carr conducted a frequency analysis of all verbal and visual references to alcohol on the televised Formula 1 Monaco Grand Prix 2014 (O’Brien 2015), demonstrating on average, 11 promotional references to alcohol per minute during the race.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol-branded merchandise or alcohol promotional items represent another way that alcohol companies increase brand exposure among young people (Jones 2016; McClure 2006). Youth and young adults are further exposed to alcohol marketing through sponsorship of sports teams and events (Macniven 2015). Authors of a systematic review found positive associations between exposure to alcohol sports sponsorship and increased levels of consumption, including two studies reporting significant associations between exposure to sports sponsorship and increased levels of consumption among children (Brown 2016).…”
Section: Introductionmentioning
confidence: 99%